Application of the Schwartz method to the calculation of waveguide PAA in the presence of die-lectric inserts and coatings - Gnatyuk, M.A.; Morozov, V.M. (Radiotekhnika, 2017)
The application of the Schwarz method for solving the problem of diffraction of an electromagnetic wave on a linear phased array antenna scanning in the H-plane is considered. The diffraction problem is reduced to the solution of the Fredholm integral equation of the second kind by the method of successive approximations. Expressions are obtained for the reflection coefficient of the incident wave in the i-order approximation.